Melatonin integrates multidimensional regulation of Na+/K+-ATPase in ionocytes and promotes stress and ease response in hypoxia-induced air-breathing fish: lessons from integrative approach - Peter, M. C. Subhash; Gayathry, R.; Simi, S.; Peter, Valsa S. (Frontiers in Physiology, 2023)
As circadian regulator, melatonin is involved in many physiological processes including ionosmotic regulation in fishes. Na+/K+-ATPase (NKA), an ubiquitous Na+/K+ transporter in ionocyte epithelia that drives electrochemical Na+ gradients and systemic osmotic integration, is a target of stress in fish. However, it is not certain how melatonin regulates NKA functions in ionocyte epithelia and how it modulates the adaptive response such as stress and ease response in fish particularly in hypoxia condition. We, thus, examined the short-term in vivo action of melatonin on the dynamics of NKA regulation in branchial, renal and intestinal ionocytes of hypoxia-induced air-breathing fish (Anabas testudineus Bloch). Interestingly, we found a rise in plasma melatonin in fish when kept for 30 min of forced submergence in water and that indicates a role for melatonin in hypoxia tolerance. A fall in blood [Na+, K+] occurred in these hypoxic fish which later showed a recovery after melatonin treatment. Similarly, melatonin favored the fall in NKA activity in branchial and renal epithelia of hypoxic fish, though it remarkably stimulated its activities in non-stressed fish. Likewise, melatonin that produced differential pattern of mRNA expression in nkaα1-subunit isoforms (nkaα1a, nkaα1b and nkaα1c) and melatonin receptor isoforms (mtnr1a, mtnr1bb, mtnr1bbx1x2) in the tested ionocyte epithelia, showed reversed expression in hypoxic fish. In addition, the rise in NKAα-protein abundance in branchial and renal epithelia of melatonin-treated hypoxic fish indicated a recovery action of melatonin. A higher NKAα-immunoreactivity was found in the immunohistochemical and immunofluorescent images of branchial ionocytes and renal proximal and distal ionocytes of hypoxic fish treated with melatonin. Furthermore, an activation of PKA and PKG-dependent phosphorylation was found in branchial epithelia of hypoxic fish. The generated integrative parabola model showed that melatonin has a maximum targeted action on NKA function in the renal epithelia, suggesting its lead role in the integration of ionosmotic balance during the recovery or ease response. Over all, the data indicate a multidimensional and preferential action of melatonin on NKA regulation in fish ionocytes that integrate the recovery action against hypoxia, thus pointing to a major role for melatonin in stress and ease response in this fish.